1998
DOI: 10.1080/095851998340739
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance strategies and the German system of co-determination

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 4 publications
1
59
1
4
Order By: Relevance
“…However, as indicated by case studies (Mueller, 1998;Royle, 1998;Raess and Burgoon, 2006), there may be opposing effects resulting in a negative interaction. First, important decisions are made by managers of the foreign parent company and not by managers of the local establishment.…”
Section: The Interaction With Foreign Ownersmentioning
confidence: 99%
“…However, as indicated by case studies (Mueller, 1998;Royle, 1998;Raess and Burgoon, 2006), there may be opposing effects resulting in a negative interaction. First, important decisions are made by managers of the foreign parent company and not by managers of the local establishment.…”
Section: The Interaction With Foreign Ownersmentioning
confidence: 99%
“…This work suggests that more successful outcomes emerge from codetermination when relations between council and management are cooperative. More pointedly, a series of case studies emphasize that cooperation between managers and works councils is less likely when the establishment has foreign ownership (Mueller 1998, Raess and Burgoon 2006, Royle 1998, Wever 1995. Indeed, Jirjahn and Mueller (2011) show that cooperative relationships are harder to achieve in foreign owned establishments and estimate a negative interaction effect of works councils and foreign ownership on productivity.…”
Section: Work Councils and Variable Paymentioning
confidence: 99%
“…In the German subsidiaries they study, Temple et al, (2006) found that each subsidiary successfully undertook actions attempting to free themselves from representative worker organizations that placed restrictions on their autonomy. These actions can be crucial for unilaterally implementing pay policies and are among those catalogued earlier by Ferner and Edwards (1995) and Royle (1998): co-opting works councils, manipulating formal provisions governing works councils, bypass strategies, seeking independent agreements and moving within the vast German bargaining structure to gain advantage. Such actions may be even more likely if headquarters management has little experience with codetermination causing them to view works councils simply as an obstacle.…”
mentioning
confidence: 99%
“…Fajana (2006) maintains that the principal reason for establishing a grievance handling scheme for unorganized workers may be to keep off trade unionism. Case studies have reported global policies on union avoidance in the multinationals and in extreme instances such policies have been moderated only minimally by host country regulations (Royle, 1998). Union avoidance strategies or substitution tactics include less job creation which is adopted to reduce the prospective number of employees that are likely to form or join union in multinational companies (Aamodt, 1999).…”
Section: Staff Resourcing and Outcome Of Autonomy And Controlmentioning
confidence: 99%